A computer-assisted navigation technique to perform bone tumor resection without dedicated software. Issue 1 (1st January 2016) - Zoccali, Carmine; Walter, Christina M.; Favale, Leonardo; Di Francesco, Alexander; Rossi, Barbara
Abstract: Purpose: In oncological orthopedics, navigation systems are limited to use in specialized centers, because specific, expensive, software is necessary. To resolve this problem, we present a technique using general spine navigation software to resect tumors located in different segments. Materials and Methods: This technique requires a primary surgery during which screws are inserted in the segment where the bone tumor is; next, a CT scan of the entire segment is used as a guide in a second surgery where a resection is performed under navigation control. We applied this technique in four selected cases. To evaluate the procedure, we considered resolution obtained, quality of the margin and its control. Results: In all cases, 1 mm resolution was obtained; navigation allowed perfect control of the osteotomies, reaching the minimum wide margin when desired. No complications were reported and all patients were free of disease at follow-up (average 25.5 months). Conclusions: This technique allows any bone segment to be recognized by the navigation system thanks to the introduction of screws as landmarks. The minimum number of screws required is four, but the higher the number of screws, the greater the accuracy and resolution. In our experience, five landmarks, placed distant from one another, is a good compromise. Possible disadvantages include the necessity to perform two surgeries and the need of a major surgical exposure; nevertheless, in our opinion, the advantages of better margin control justify the application of this technique in centers where an intraoperative CT scanner, synchronized with a navigation system or a dedicated software for bone tumor removal were not available.